10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BackgroundCleft lip and palate (CLP) are common congenital craniofacial anomalies associated with substantial health and psychosocial burdens. Although maternal smoking during pregnancy has been linked to CLP, observational studies cannot establish causality because of confounding and reverse causation.MethodsWe performed a two-sample Mendelian randomization (MR) study to investigate the causal effect of maternal smoking on offspring CLP. Genetic variants associated with maternal smoking were used as instrumental variables. Summary statistics were obtained from the UK Biobank (maternal smoking) and the FinnGen consortium (CLP). The primary analysis used the inverse-variance weighted (IVW) method, with MR-Egger and weighted median analyses conducted as sensitivity analyses.ResultsIVW analysis demonstrated a significant causal association between maternal smoking and CLP (b = 5.34, SE = 2.50, p < 0.05). Sensitivity analyses yielded consistent results and showed no evidence of substantial heterogeneity or horizontal pleiotropy, supporting the robustness of the findings.ConclusionsOur findings provide genetic evidence supporting a causal relationship between maternal smoking and CLP. These results reinforce the importance of smoking cessation during pregnancy and support public health strategies aimed at reducing preventable risk factors for CLP. Further studies are warranted to investigate the underlying biological mechanisms and validate these findings in diverse populations.